COMPARISON OF ENERGY FLOWS IN DEEP-INELASTIC SCATTERING EVENTS WITH AND WITHOUT A LARGE RAPIDITY GAP - Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Repond, J; Schlereth, J; Stanek, R; Talaga, R; Thron, J; Arzarello, F; Ayad, R; Bari, G; et al. (1994)
Energy flows in deep inelastic electron-proton scattering are investigated at a centre-of-mass energy of 296 GeV for the range Q2 ≥ 10 GeV2 using the ZEUS detector. A comparison is made between events with and without a large rapidity gap between the hadronic system and the proton direction. The energy flows, corrected for detector acceptance and resolution, are shown for these two classes of events in both the HERA laboratory frame and the Breit frame. From the differences in the shapes of these energy flows we conclude that QCD radiation is suppressed in the large-rapidity-gap events compared to the events without a large rapidity gap.